Significant urban farm resources developed by the Great Lakes Urban Ag IPM Working Group - Margaret Rivera; Jacqueline Kowalski; Laura L Ingwell; James Jasinski (Urban Food Systems Symposium, 2024)
Urban agriculture, the ability of community members to engage in growing food, is the crux of a just urban food system. The Great Lakes Urban Ag IPM Working Group was established with support from the North Central IPM Center in 2017. The mission of the group is to create a network of university researchers and extension educators who collaborate with growers to solve production and pest management challenges on urban farms, using an integrated pest management (IPM) approach. Membership includes Extension professionals, community organizations and garden managers, partnering support agencies and farmers themselves. Through the participation of over 35 people from eight states across the region we have worked collaboratively to provide a set of tools to manage a range of crop production and pest challenges. Products created include fifteen pest cards, available in both Spanish and English, which provide identification and management recommendations. These cards have been disseminated across several states and posted online. A webinar series provided specialists the opportunity to talk about scouting and trapping for insect pests, composting with black soldier flies and a unique 360-degree virtual urban ag farm tour project. The virtual tours allow anyone to “visit” and experience the diversity of urban farms. Key production and pest management information is highlighted within the virtual tour by information icons. There is currently a library of seventeen 360-degree urban farm tours which originated in Ohio but have recently expanded to highlight urban farms in MI, IN and IL. Our group continues to build collaborations and create resources to train urban farmers in pest management. In this paper, we will share information about the resources we have made, including how to access them, and discuss the structure and function of the collaboration.
Keywords: diversity; integrated pest management; urban agriculture